The philosophical values of Rejang Dayung as an ancient dance inherited from Pura Luhur Batukau, Tabanan, Bali - Dana, I Wayan; Alfirafindra, Raja; Anggraeni, Agustin (Gelar: Jurnal Seni Budaya, 2023)
Rejang Dayung is an ancient dance inherited from the ancestors, serving a ritualistic function at Pura Luhur Batukau. It is exclusively performed in Jaba Tengah or the media mandala (living room) during the Sinineban (closing) ceremony at Pura Luhur Batukau. Noteworthy for its straightforward expressions in movements, floor patterns, costumes, and accompaniment, this dance merits scholarly investigation. The objectives of this study are to elucidate the philosophical value of Rejang Dayung performance as an ancient dance inherited from Pura Luhur Batukau, examine the correlation between the philosophical value of Rejang Dayung and the societal beliefs of Pura Luhur Batukau, and expound upon the significance of Rejang Dayung's philosophical value based on the concepts of Satyam (truth), Shivam (holiness), and Sundaram (beauty). The authors employed a qualitative method, incorporating field observation and interview techniques to gather data and ascertain the initial presentation of Rejang Dayung. The study's findings unequivocally reveal the philosophical values of Rejang Dayung and the embodiment of the Tri Hita Karana teachings (Balinese concepts for creating harmony), which encompass harmonious relationships between humans and God, humans and fellow humans, and humans and the universe. The philosophical value of Rejang Dayung signifies a profound surrender to the magnificence of Ida Sanghyang Widhi Wasa, God the Greatest, manifested through the collective choreography in pairs, symbolizing the convergence of Shiva-Parwati energy. This convergence, perceived by the people of Pura Luhur Batukau as the guardian of harmony in the universe and its constituents, underscores the dance's cultural and spiritual significance.